Aneurismas coronarios en la enfermedad de Kawasaki - Amilachwari B, Miguel; Yanira Rueda, Gloria; Kovalski, Sonia; Orta Ferrer, Lorgia; Pérez A, Saúl (Gaceta Médica de Caracas, 2021)
Se procede al análisis de la literatura médica en relación al impacto que representa en la enfermedad de Kawasaki, la presencia y trascendencia de los aneurismas coronarios, especialmente entre la población pediátrica. We present an analysis of the medical literature related to the presence and transcendency of coronary aneurysms in Kawasaki’s disease, especially in the pediatric population.